Trichloroacetic acid/acetone precipitation method to optimize canine synovial fluid for one and two-dimensional gel electrophoresis studies - Tan, Wei Miao; Seng, Fong Lau; Syed Sulaiman, Syarifah Zakiah; Umran, Nor Shahira Solehah; Ajat, Mokrish; Mansor, Rozaihan; Megat Abdul Rani, Puteri Azaziah; Shafie, Intan Nurfatiha; Ng, Angela Min Hwei; Rahmad, Norasfaliza (Universiti Kebangsaan Malaysia, 2021)
The challenge associated with the use of synovial fluid for osteoarthritic proteome studies is the optimization step, which involves the depletion of high abundant proteins from the samples. The objective of this study was to develop a cost efficient and effective method to remove albumin from canine synovial fluid for proteome studies. Pooled synovial fluid samples were obtained from clinically healthy dogs (n=5), with no radiographic features of osteoarthritis. The acetone precipitation method and 10% w/v of trichloroacetic acid/acetone were chosen to deplete the albumin from canine synovial fluid and the outcome from the different methods were compared using one dimensional and twodimensional gel electrophoresis studies. The results showed that the 10% w/v TCA/acetone precipitation method removed highly abundant proteins from synovial fluid for gel electrophoresis studies compared to the acetone precipitation method. The 10% w/v TCA/acetone precipitation method provides an effective method to remove albumin from the synovial fluid using gel electrophoresis, especially two-dimensional gel electrophoresis. The accessibility and cost of TCA and acetone make this method of precipitation a simple and cost-effective technique in preparing a canine synovial fluid for two-dimensional gel electrophoresis analysis.